2012
DOI: 10.1021/np300231f
|View full text |Cite
|
Sign up to set email alerts
|

Palau’amine and Related Oroidin Alkaloids Dibromophakellin and Dibromophakellstatin Inhibit the Human 20S Proteasome

Abstract: We report herein that the oroidin-derived alkaloids, palau’amine (1), dibromophakellin (2) and dibromophakellstatin (3) inhibit the proteolytic activity of the human 20S proteasome as well as the i20S immunoproteasome catalytic core. Palau’amine is found to prevent the degradation of ubiquitinylated proteins, including IκBα, in cell culture, which may be indicative of the potential mechanism by which these agents exhibit their exciting cytotoxic and immunosuppressive properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 52 publications
1
38
0
4
Order By: Relevance
“…35,39 We found that only compound 2 induced the activation of the chymotrypsin-like (CT-L, EC 50 4.9 μ M), tryptic-like (T-L, EC 50 10.0 μ M), and caspase-like (Casp-L, EC 50 4.8 μ M) activity (Figure S2). The parallel effects of all proteolytic sites is consistent with the induction of an open-gate conformation that allows all substrates to enter the chamber.…”
mentioning
confidence: 90%
“…35,39 We found that only compound 2 induced the activation of the chymotrypsin-like (CT-L, EC 50 4.9 μ M), tryptic-like (T-L, EC 50 10.0 μ M), and caspase-like (Casp-L, EC 50 4.8 μ M) activity (Figure S2). The parallel effects of all proteolytic sites is consistent with the induction of an open-gate conformation that allows all substrates to enter the chamber.…”
mentioning
confidence: 90%
“…Pyrrole-containing molecules include commonly naturally produced compounds such as chlorophyll, chlorins, vitamin B12 and porphyrinogens [34][35][36]. A pyrrole ring is also a part of tryptamines including serotonin, melatonin and many other biologically important substances [37][38][39][40]. For that reason, apart from broadening our knowledge of the stacking interaction phenomenon itself, this extensive study of the intermolecular interaction in model pyrrole systems may be relevant in electronic properties of pyrrole-unit-based drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[10] In our ongoing efforts to discover proteasome inhibitors with novel modes of action, we investigated compounds from the highly diverse family of biologically active pyrroleimidazoline marine alkaloids, which differ significantly from all CP inhibitors described to date (Scheme 1). [14] The structurally related natural products dibromophakellstatin (2) and dibromophakellin (3) are synthetically more accessible, although these compounds display reduced CP inhibitory potency compared to 1 [IC 50 (b5c) = 25.3 and 11.9 mm, respectively]. [11][12][13] Compound 1 was described to bind irreversibly to the CP (IC 50 (b5c) = 2.5 mm), but its scarcity and structural complexity prevents the rapid generation of more potent synthetic or semisynthetic derivatives.…”
mentioning
confidence: 99%
“…The most important member of this class of compounds is palauamine (1), a cytotoxic and immunosuppressive hexacyclic bisguanidine that was isolated from the sea sponge Stylotella agminata. [14,15] We established a robust synthetic route towards derivatives of phakellins that share the same rigid cyclic framework [14,16] and revealed activity similar to 1. [14] The structurally related natural products dibromophakellstatin (2) and dibromophakellin (3) are synthetically more accessible, although these compounds display reduced CP inhibitory potency compared to 1 [IC 50 (b5c) = 25.3 and 11.9 mm, respectively].…”
mentioning
confidence: 99%